Elite and viremic HIV-1 controllers in West Africa. (1st January 2022) - N'takpé, Jean Baptiste; Gabillard, Delphine; Moh, Raoul; Gardiennet, Elise; Toni, Thomas-d'Aquin; Kouame, Gérard M.; Badje, Anani; Emieme, Arlette; Karcher, Sophie; Le Carrou, Jérome; Ménan, Hervé; Danel, Christine; et al.
Abstract : Background: Data on HIV-1 controllers in Africa are scarce. We report the proportion of HIV-1 controllers in a group of adults prospectively monitored with frequent viral load measurements as part of a clinical trial in West Africa. Methods: For the Temprano trial, antiretroviral therapy (ART)-naive HIV-1 infected adults with no criteria for starting ART were randomized to start ART immediately or defer ART until the WHO starting criteria were met. Plasma viral load was measured every 6 months. The trial follow-up was 30 months. We considered all Temprano participants randomized to defer ART. Patients with all semestrial viral <2000 copies/ml and still off ART at month 30 were defined as HIV-1 controllers. Controllers with all viral loads <50 copies/ml were defined as elite controllers, the rest as viremic controllers. Results: Of the 1023 HIV-1-infected adults randomized in the Temprano deferred-ART group, 18 (1.8%) met the criteria for classification as HIV controllers, of whom seven (0.7%) were elite controllers and 11 (1.1%) viremic controllers. The HIV-1 controllers had low peripheral blood mononuclear cell HIV-1 DNA and low inflammatory marker levels. They maintained high CD4 + cell count and percentages and had a low morbidity rate. Discussion: HIV controllers exist in Africa at a proportion close to that reported elsewhere. They represent a small fraction of all HIV-1-infected patients but raise important questions. Further studies should assess whether starting ART might represent more risk than benefit for some controllers, and where it does, how to identify these patients before they start ART.